Oceania's political institutions and transitions - Fraenkel, Jon (2010)
The Pacific Islands region includes entities closely incorporated with the metropolitan powers located around the Pacific Rim, such as Guam (USA), Rapa Nui (Chile) and Tokelau (New Zealand), as well as independent states like Papua New Guinea, Fiji and Kiribati. The region includes countries that achieved independence less than thirty years ago as well as those still in the process of adjustment to the post-colonial order. It includes resource-rich territories with strong potential for integration into the world economy alongside chronically resource-poor countries with limited avenues for export-driven economic growth. ...